(untitled) (Journal on Geoinformatics, Nepal, 2017)
Sub-Watershed management and planning is integration of both technical and social aspects. Physical assessment of sub-watershed includes among many other bio-physical parameters, the morphometric analysis. The current study examines the applicability of existing stream order digital data for morphometric analysis and sub-watershed prioritization of Kailash Khola watershed. The study is based on secondary data and desk study and uses GIS data produced by Survey Department of Nepal and GIS tool for the analysis. Three linear and three aerial/shape parameters are taken for the morphometric analysis and simple ranking method based on calculated value is applied for sub-watershed prioritization. Technological tools like GIS and Remote Sensing has aided for spatial analysis using morphometric method. The study show that variation is found in vulnerability of sub-watershed in terms of linear and aerial morphometric parameters. The finding show that western part of the watershed is relatively vulnerable in terms of potential soil erosion and flooding. The study concludes that the importance of readily available stream order digital data and GIS tool and technology in identifying and analyzing priority subwatershed is reasonable. However, it is realized that spatial data at more finer spatial scale will improve the analysis and provide better analysis result and exemplify local problems in the area of topographical variation. The study suggest that, introduction of stream order data set finer scale or will allow analysis to be performed at much greater so that more localized effect of drainage morphometry in varying topographical landscape of the country could be assessed.